Contractual Freedom and Economic Conditions: The Case of Standardized Employment Contracts - Bjaloňová, Michaela (Technium Social Sciences Journal, 2025)
The paper examines the principle of contractual freedom in employment relationships, with particular emphasis on its practical limitations. Contractual autonomy is analyzed within a broader socio-economic and legal context, highlighting the inherent asymmetry between employers and employees. The study demonstrates how economic factors, notably unemployment rates and labor market conditions, shape employees’ bargaining power and constrain their ability to effectively exercise contractual freedom. The paper underscores the necessity of considering not only legal norms but also socio-economic determinants when evaluating the scope of contractual freedom in labor law, emphasizing the interplay between formal rights and their practical enforceability.